(untitled) (Research, Society and Development, 2021)
Objective: Conduct a survey about the epidemiological scenario of HIV/Aids in Alagoas. Method: This is a descriptive epidemiological study with a quantitative approach on the scenario of HIV and Aids in the state of Alagoas from 2009 to 2018, using secondary data from SINAN through the Aids Notification / Investigation Form (patients aged 13 or over) available by the Health Department of the State of Alagoas (SESAU), tabulated in electronic spreadsheet (Microsoft Excel®) and analyzed statistically using the Statistical Package for the Social Sciences (SPSS) 22.0. The constituent variables of this study are sociodemographic data, HIV transmission routes, criteria for defining cases of HIV/Aids and evolution of reported cases. Results: Were reported 7,447 cases of HIV and Aids in the observed period, with 62.9% of males and 37.1% of females, with an average age of 35 years, with 71.5% of people of race/color brown and 44.5% of people who are illiterate or who have completed elementary school only. The most frequent category of exposure was heterosexual, considerably higher among women. Of the 102 municipalities belonging to the state of Alagoas, 96 of them (94.12%) presented cases of HIV and Aids. The study also reveals that there is an annual increase in the number of new diagnosed HIV cases and a decrease in the number of deaths from Aids. Conclusion: The epidemiological profile of HIV/Aids in Alagoas is permeated by the processes of social and gender vulnerability, with the scenario showing trends of interiorization, youth, feminization and impoverishment throughout the analyzed historical serie.